Impaired PSII Proteostasis Promotes Retrograde Signaling via Salicylic Acid. Issue 4 (3rd June 2019) - Duan, Jianli; Lee, Keun Pyo; Dogra, Vivek; Zhang, Siyuan; Liu, Kaiwei; Caceres-Moreno, Carlos; Lv, Shanshan; Xing, Weiman; Kato, Yusuke; Sakamoto, Wataru; Liu, Renyi; Macho, Alberto P.; et al.
Abstract : Accumulation of photodamaged PSII core proteins enables retrograde signaling via the stress hormone salicylic acid and its signaling components, EDS1 and PAD4. Abstract: Photodamage of the PSII reaction center (RC) is an inevitable process in an oxygen-rich environment. The damaged PSII RC proteins (Dam-PSII) undergo degradation via the thylakoid membrane-bound FtsH metalloprotease, followed by posttranslational assembly of PSII. While the effect of Dam-PSII on gene regulation is described for cyanobacteria, its role in land plants is largely unknown. In this study, we reveal an intriguing retrograde signaling pathway by using the Arabidopsis ( Arabidopsis thaliana ) yellow variegated2-9 mutant, which expresses a mutated FtsH2 (FtsH2 G267D ) metalloprotease, specifically impairing its substrate-unfolding activity. This lesion leads to the perturbation of PSII protein homeostasis (proteostasis) and the accumulation of Dam-PSII. Subsequently, this results in an up-regulation of salicylic acid (SA)-responsive genes, which is abrogated by inactivation of either an SA transporter in the chloroplast envelope membrane or extraplastidic SA signaling components as well as by removal of SA. These results suggest that the stress hormone SA, which is mainly synthesized via the chloroplast isochorismate pathway in response to the impaired PSII proteostasis, mediates the retrograde signaling. These findings reinforce the emerging view of chloroplast function toward plant stress responses and suggest SA as a potential plastid factor mediating retrograde signaling.